Understanding Fake News: An Interdisciplinary Approach: Array - Hagiu, Adrian; Bortoș, Sergiu (Acta Universitatis Danubius. Communicatio, 2021)
In this paper, we made a distinction between the concept of fake news and the phenomenon of fake news. Since there are several definitions of fake news, we noticed that the concept is often confused with the phenomenon. Using the philosophical method proposed by R.G. Collingwood, we proved that fake news can be approached as a philosophical concept. At the same time, we also analysed the fake news phenomenon, through which we highlighted its effects on daily life. In a first stage, we reviewed several definitions and theoretical aspects related to fake news, then we argued that this distinction leads to a second one: between combating and prevention. If in the case of the phenomenon we refer to a post-factum combat, then in the case of the concept, we can prevent the phenomenon following a good theoretical knowledge of it. The interdisciplinary approach we proposed in this paper with a focus on studying fake news has the advantage of opening the field of analysis, and the clarification we made can be a starting point in differentiating between theory and practice when the issue of fake news is studied.